Resting‐state brain fluctuation and functional connectivity dissociate moral injury from posttraumatic stress disorder. Issue 5 (28th January 2019) - Sun, Delin; Phillips, Rachel D.; Mulready, Hannah L.; Zablonski, Stephen T.; Turner, Jessica A.; Turner, Matthew D.; McClymond, Kathryn; Nieuwsma, Jason A.; Morey, Rajendra A.
Abstract: Moral injury is closely associated with posttraumatic stress disorder (PTSD) and characterized by disturbances in social and moral cognition. Little is known about the neural underpinnings of moral injury, and whether the neural correlates are different between moral injury and PTSD. A sample of 26 U.S. military veterans (two females: 28–55 years old) were investigated to determine how subjective appraisals of morally injurious events measured by Moral Injury Event Scale (MIES) and PTSD symptoms are differentially related to spontaneous fluctuations indexed by amplitude of low frequency fluctuation (ALFF) as well as functional connectivity during resting‐state functional magnetic resonance imaging scanning. ALFF in the left inferior parietal lobule (L‐IPL) was positively associated with MIES subscores of transgressions, negatively associated with subscores of betrayals, and not related with PTSD symptoms. Moreover, functional connectivity between the L‐IPL and bilateral precuneus was positively related with PTSD symptoms and negatively related with MIES total scores. Our results provide the first evidence that morally injurious events and PTSD symptoms have dissociable neural underpinnings, and behaviorally distinct subcomponents of morally injurious events are different in neural responses. The findings increase our knowledge of the neural distinctions between moral injury and PTSD and may contribute to developing nosology and interventions for military veterans afflicted by moral injury.